2006
DOI: 10.1021/cc0501108
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening and Optimization of Photoembossed Relief Structures

Abstract: A methodology for the rapid design, screening, and optimization of coating systems with surface relief structures, using a combination of statistical experimental design, high-throughput experimentation, data mining, and graphical and mathematical optimization routines was developed. The methodology was applied to photopolymers used in photoembossing applications. A library of 72 films was prepared by dispensing a given amount of sample onto a chemically patterned substrate consisting of hydrophilic areas sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Advanced data handling allowing facile visualization and/or mathematical description of the structure-processingproperty relationships present in the dataset. [72] After performing these five steps, one may use the obtained knowledge, the questions remaining, and/or the new questions that arose from the combinatorial experiment to design the next combinatorial experiment. [69] Alternatively, one can ''zoom in'' to a part of the parameter space that showed interesting ''leads'' or ''hits'', to identify even more optimal results by a finer-meshed investigation of that part of the parameter space.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced data handling allowing facile visualization and/or mathematical description of the structure-processingproperty relationships present in the dataset. [72] After performing these five steps, one may use the obtained knowledge, the questions remaining, and/or the new questions that arose from the combinatorial experiment to design the next combinatorial experiment. [69] Alternatively, one can ''zoom in'' to a part of the parameter space that showed interesting ''leads'' or ''hits'', to identify even more optimal results by a finer-meshed investigation of that part of the parameter space.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
“…[73,74] Design of experiment (step 1), advanced data handling (step 5), and proper integration of all steps of the combinatorial workflow significantly improve the information output of the experiment. [72] During combinatorial experiments, many different materials are made (step 2) but the amount of sample for each material is generally small. Typically, polymer amounts of 100 mg (an example from a polyolefin catalyst optimization study by Boussie et al [74] ) to 500 mg (sequential robot-assisted cationic ring-opening polymerization by Hoogenboom et al [75] ) are synthesized.…”
Section: High-throughput Experimentationmentioning
confidence: 99%
“…In current photoembossing, the aspect ratio, defined as the ratio of height and width, is typically less than 1/20 for a 40 m periodic line structure. 7,8 It was found that the material flux, and thus the aspect ratio, is highly affected by the polymerization kinetics and can be optimized by changing the rate of initiation via altering initiator content or light intensity. 9 It is the objective of our present research to improve the aspect ratio even further.…”
mentioning
confidence: 99%
“…Surface topographies and reliefs can be created in multiple ways, either by physically imprinting (embossing [15,16]) or by manipulation of the material itself using light, temperature, pH, and/or solvent-swelling. Interestingly, light allows for a remote, contactless approach without changing the chemical environment.…”
Section: Introductionmentioning
confidence: 99%